The Lithography: Manipulative Element Conducive to the Commercial Sale of the Nineteenth Century of Peru - Delgado Del Aguila, Jesús M. (2021)
This paper is based on the social analysis of the consumer consciences of the country during the turn of the century. The magazine The Ilustred Peru (1887-1892), directed by Bacigalupi and Matto de Turner, is taken as a reference to demonstrate the functionality of the press by promoting and reorienting culture towards a materialistic approach. On the one hand, through the tense semiotics developed by Jacques Fontanille, relevant meanings originate from the fields of expression and content, essential to investigate to understand the purpose of advertising images. Likewise, through Landowski's regimes of meaning (manipulation and programming), it is evident how a fashion is established in consumers due to their claim to acquire the products that are subjected to the sale of the market.